Higher Flexibility and Better Immediate Spontaneous Correction May Not Gain Better Results for Nonstructural Thoracic Curve in Lenke 5C AIS Patients: Risk Factors for Its Correction Loss. Issue 22 (15th November 2016) - Zhang, Yanbin; Lin, Guanfeng; Wang, Shengru; Zhang, Jianguo; Shen, Jianxiong; Wang, Yipeng; Guo, Jianwei; Yang, Xinyu; Zhao, Lijuan
Abstract : Study Design: Retrospective study. Objective: To study the behavior of the unfused thoracic curve in Lenke type 5C during the follow-up and to identify risk factors for its correction loss. Summary of Background Data: Few studies have focused on the spontaneous behaviors of the unfused thoracic curve after selective thoracolumbar or lumbar fusion during the follow-up and the risk factors for spontaneous correction loss. Methods: We retrospectively reviewed 45 patients (41 females and 4 males) with AIS who underwent selective TL/L fusion from 2006 to 2012 in a single institution. The follow-up averaged 36 months (range, 24–105 months). Patients were divided into two groups. Thoracic curves in group A improved or maintained their curve magnitude after spontaneous correction, with a negative or no correction loss during the follow-up. Thoracic curves in group B deteriorated after spontaneous correction with a positive correction loss. Univariate analysis and multivariate analysis were built to identify the risk factors for correction loss of the unfused thoracic curves. Results: The minor thoracic curve was 26° preoperatively. It was corrected to 13° immediately with a spontaneous correction of 48.5%. At final follow-up it was 14° with a correction loss of 1°. Thoracic curves did not deteriorate after spontaneous correction in 23 cases in group A, while 22 cases were identified with thoracic curve progressing in group B. In multivariate analysis, two risk factors were independently associated with thoracic correction loss: higher flexibility and better immediate spontaneous correction rate of thoracic curve. Conclusion: Posterior selective TL/L fusion with pedicle screw constructs is an effective treatment for Lenke 5C AIS patients. Nonstructural thoracic curves with higher flexibility or better immediate correction are more likely to progress during the follow-up and close attentions must be paid to these patients in case of decompensation. Level of Evidence: 4